Studying Sodium Hypochlorite Usages among Syrian Dentists in Managing Different Endodontic Procedures (Journal of Hama University, 2020)
Background : Endodontic instruments aren’t able to completely mange the root canal system unless they're supported with irrigant solutions backup. This study aims to evaluate different irrigant solutions used in managing endodontic conditions in both adults and children by Syrian dentists.  Methods : 400 surveys, including 15 questions about irrigant solutions; were distributed to dental practitioners between the 5th and 8th of November 2018 in Damascus. Descriptive and analytic statistics were performed with SPSS 17.0, using non parametric Chi-square and Fisher's exact tests at 0.05 significance level.Results : 295 dentists were included in the study. NaOCl was favoured by 89.8% of participants. 47.8% preferred it with concentrations varying between 1.6% and 5%.Non parametric Chi-square and Fisher's exact tests revealed significant differences among irrigant used during various endodontic procedures toward NaOCl in both adults and children (P